-15+t=30-2t

Simple and best practice solution for -15+t=30-2t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15+t=30-2t equation:



-15+t=30-2t
We move all terms to the left:
-15+t-(30-2t)=0
We add all the numbers together, and all the variables
t-(-2t+30)-15=0
We get rid of parentheses
t+2t-30-15=0
We add all the numbers together, and all the variables
3t-45=0
We move all terms containing t to the left, all other terms to the right
3t=45
t=45/3
t=15

See similar equations:

| 25+3a=150 | | -6g=14=-12-8g | | n+9=44 | | x2−14x+44=0 | | -9a^2+15=0 | | 4.2v+1.8=54 | | 16x+26=24 | | |x+3|=2x+1 | | 2x2/3=8 | | 4(2x+3)-x+1=31 5 45 | | 0.01+0,01x=0,1x | | 8(3x+2)-16=192 | | (t/3)t^2-25=0 | | 5/3x1/3x=51/3+7/3x | | 11+8n=51 | | -v/6=50 | | 0.01+0.01x=0,01x | | -3x-7=×+21 | | c6c+14=4+4c | | -43=-v/7 | | 1/2x+1/4=1/6 | | (1/4)(3x-1)+(1/6)(x+3)=3 | | 10x^2+60x=1600 | | 5(7x+1)-30=220 | | 6-2x=5x-9x=16 | | -5z(-14z)-(-9z)-3z=-15 | | 5=m-5+0 | | -18+b=8(-4+b) | | 2(×+3)=2x+6 | | X÷2-4=2x-37 | | ​9/4​​y−12=​4​​1​​y−4 | | 32n=192 |

Equations solver categories